PLANNING AND DESIGNING THE CREATIVE INDUSTRY AND START-UP CO-WORKING SPACE IN SURAKARTA - Farah, Nabila Hanif; Hardiana, Ana; Muqoffa, Mohamad (Universitas Sebelas Maret Surakarta, 2018)
Surakarta City is designated as National Activity Center (PKN) on the National Spatial Plan (RTRWN) in the development of the creative economy sector. The determination is reinforced by Bekraf Developer Day 2017 and the Economic Census of the Central Bureau of Statistics which shows that Surakarta has more than 1250 creative workers. 65.75% of them have no place to work, so they do their work at home and or cafe. Problems that arise are how to design facilities and comfortable workspace so that the creative workers can make presentations and discussions with colleagues without being disturbed by the noise of other cafe visitors, or by family activities at home. In order to connect between start-up and creative workers, and to create a comfortable workspace to improve productivity and creativity of its users, is required collaborative working space (office) for creative industry workers and start-up in Surakarta City. The design of collaborative working space is done by collecting primary and secondary data through interviews, observation, precedent study, book literature study, local regulations, articles, and news. The data sets are then analyzed and synthesized to produce the concept of the space character criteria and the concept of the shape and appearance of the space which is then transformed into a collaborative working space design that supports the productivity and creativity of its users in Surakarta.